INO1-100: an allele of the Saccharomyces cerevisiae INO1 gene that is transcribed without the action of the positive factors encoded by the INO2, INO4, SWI1, SWI2 and SWI3 genes. - Swift, S (1995)
A dominant allele of the INO1 locus, INO1-100, does not require the positive regulators encoded by INO2 and INO4 for expression. Sequence analysis showed that INO1-100 had a 239 bp deletion in the INO1 promoter. INO1-100 suppressed the inositol auxotrophy of ino2, ino4, swi1, swi2 and swi3 mutants. Transcription of INO1-100 was constitutive and independent of these regulators. A 20 bp deletion from -247 to -228 caused a similar phenotype. A 38 bp deletion from -245 to -208 suppressed the inositol auxotrophy of an ino2 mutant, but not an ino4 mutant, indicating that Ino2p and Ino4p may function alone as well as in a complex. A 40 bp deletion from -287 to -248 that removed a URS1 site caused constitutive transcription that required INO2 and INO4. A deletion from -167 to -128 suppressed the inositol auxotrophy of swi, ino2 and ino4 mutants, indicating the presence of a previously unidentified URS1. Mutation of the specific negative regulator of phospholipid synthesis encoded by OPI1 suppressed the inositol auxotrophy of swi2 mutants. This study indicates that negative regulation of INO1 is chromatin mediated and provides in vivo information on the interaction of both general and specific regulatory factors that function to accomplish negative and positive regulation of the INO1 promoter in response to inositol.